Performance Evaluation of Plain Weave and Honeycomb Weave Electrodes for Human ECG Monitoring. (5th July 2017) - Xiao, Xueliang; Pirbhulal, Sandeep; Dong, Ke; Wu, Wanqing; Mei, Xi
Abstract : Long-time monitoring of physiological parameters can scrutinize human health conditions so as to use electrocardiogram (ECG) for diagnosis of some human's chronic cardiovascular diseases. The continuous monitoring requires the wearable electrodes to be breathable, flexible, biocompatible, and skin-affinity friendly. Weave electrodes are innovative materials to supply these potential performances. In this paper, four conductive weave electrodes in plain and honeycomb weave patterns were developed to monitor human ECG signals. A wearable belt platform was developed to mount such electrodes for acquisition of ECG signals using a back-end electronic circuit and a signal transfer unit. The performance of weave ECG electrodes was evaluated in terms of skin-electrode contacting impedance, comfortability, ECG electrical characteristics, and signal fidelity. Such performances were then compared with the values from Ag/AgCl reference electrode. The test results showed that lower skin-electrode impedance, higher R-peak amplitude, and signal-to-noise ratio (SNR) value were obtained with the increased density of conductive filaments in weave and honeycomb weave electrode presented higher comfort but poorer signal quality of ECG. This study inspires an acceptable way of weave electrodes in long- and real-time of human biosignal monitoring.